A272 UTILIZING BEDSIDE ULTRASOUND TO ASSESS MUSCLE MASS IN CIRRHOTIC PATIENTS ASSESSED FOR LIVER TRANSPLANTATION. (15th March 2019) - Mandill, J; Hilwah, M; Sinclair, L; Hussam Eddin, A; Brown, C; Anwar, M; Teriaky, A; Marotta, P; Qumosani, K
Abstract: Background: Background: Muscle atrophy is present in 40% of cirrhotic patients and associated with increased morbidity and mortality in those awaiting liver transplantation (LT). There is a two-fold increase in mortality, compared to non-sarcopenic patients, independent of liver dysfunction using Model for End-Stage Liver Disease (MELD). The current Sodium MELD score does not incorporate markers of nutritional status, or muscle loss. Ultrasound is a non-invasive method to evaluate skeletal muscle and is validated and emerging as a prognostic indicator of muscle atrophy, thereby improving detection of malnutrition. Aims: Objectives: To assess quadriceps muscle layer thickness (QMLT) using ultrasound across a range of nutritional risk scores: Royal Free Hospital Nutrition Prioritizing Tool (RFNS), illness severity scores: Sodium MELD and muscle strength: Hand-Grip Strength (HGS). Methods: Methods: A prospective study from July 2016 to May 2018 was conducted using QMLT measures in 93 adult patients assessed for LT. QMLT was measured at mid-point from anterior superior iliac spine (ASIS) and patella. These measures were compared to sodium MELD scores, RFNS, and HGS. S tatistical analysis: Data were normally distributed, student t -test and Pearson correlations were performed, significance as P < .05, using SPSS. Results: Twenty three percent of patients w ere diagnosed with NASH, 20% HCV, 20% ETOH, and 37% other liver diseases. 63% males, mean age (y) ± SEM: 58.6 ±1.35, BMI 28.4 ± 0.785; 37% females: 58.2 ± 2.33, BMI 24.1 ± 0.875, p=0.001. Mean QMLT [cm], males: 8.3 ± .642 versus females: 5.9 ± 0.60 p=0.008, HGS [kg]: 35.2 ± 1.53 versus females: 22.7 ± 2.17, p=0.001. Pearson correlation (males only): QMLT with Na-MELD r= -0.460 p=0.001; HGS r=0.423 p=0.002; RFNS: r= -0.592, p=0.001. Females showed associations between QMLT and HGS r=0.761 p=0.001 and RFNS r=-0.374 p=0.029. However, there were no correlations between QMLT, and NaMELD, edema or disease type in females. Conclusions: Conclusions: In both sexes QMLT was associated with HGS and RFNS indicating as muscle mass decreases, HGS and RFNS worsens. There was a negative association between QMLT and NaMELD in males, however, in females worsening QMLT was not associated with illness severity by NaMELD, indicating assessment of muscle mass differs by gender suggesting individualized nutritional therapies in potential LT recipients. Future studies are needed to determine the relationship, if any, with QMLT scores and morbidity and mortality. Funding Agencies: None